PEMIKIRAN HADITS KH HASYIM ASY'ARI TERHADAP PENYIMPANGAN AKIDAH DI TANAH JAWA (TELA'AH ATAS KITAB RISALAH AHLUSUNNAH WAL JAMA'AH) - Maulana, Sukma (al Dhikra | Jurnal Studi Qur'an dan Hadis, 2023)
Islam is a straight religion, because it is based on revelation, both revelation from Allah, as well as revelation referred to as the hadith of the prophet. However, quite a few people misunderstand the meaning of Islamic teachings, because they start from ignorance and blind taqlid. In Indonesia itself, since the Dutch colonial era, there have been many Islamic sects that have been considered heretical and misleading. This research is motivated by the rise of deviant sects in Indonesia, especially in the pre-independence era. Apart from that, the issue of flows in Indonesia will always attract attention for research. Therefore, researchers are interested in studying this theme in more depth. This research is a library research in the form of a thematic study model that focuses on hadiths in the book Risalat Ahlusunnah wal Jama'ah by KH. Hasyim Asy'ari with a special discussion of deviations from the faith in Java. The conclusion of the article shows that deviant creeds the colonial period were very widespread. Some of the deviations from the sects in Java at that time were the emergence of the Wahhabi, Shiite, Ibahiyun, Reincarnation and Hulul/Ittihad sects. Then, in reviewing the maqasid asy-syraiah, the Ahlussunnah wal Jama'ah creed is a straight creed and several good and correct rules have been laid down in religion. Therefore, these deviant schools are not straight Islamic teachings, but only make Islamic values ??dirty.